A Cross Sectional Study of the Impact of Human Immunodeficiency Virus, Hepatitis B Virus and Hepatitis C Virus on Rheumatoid Factor Production - Etienne Atabonkeng PHILÉMON; Christopher TUME; Marie Claire OKOMO ASSOUMOU; Salomon TCHUANDOM BONSI; Ikomey Mondide GEORGES; Hervé OUAMBO FOTSO; Lyonga EMILYA; Mesembe Tonga MARTHA; Madelaine NGANDEU-SINGWE (Archives of Rheumatology, 2018)
Objectives: This study aims to investigate how human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) affect the production of immunoglobulin M (IgM)-rheumatoid factor (RF). Patients and methods: The study included 405 voluntary participants (139 males, 266 females; mean age 39.4±17.9 years; range 3 to 88 years) randomly recruited by a consecutive sampling technique in the main health facilities of the Center, East, Far North, Littoral and West regions of Cameroon. We excluded persons under treatment or hospitalized for any form of primary autoimmune disease. Blood samples were collected and used for serological analyses. We sought for the HIV antibodies (Ab); the core antibody (HBcAb), the surface antigen (HBsAg), and the replicative antigen (HBeAg) of the HBV; HCVAb of HCV and the IgM-RF. Results: The prevalence of HIVAb was 7.61%, 38.7% for HBcAb, 5.43% for HBsAg, 1.26% for HBeAg and 6.41% for IgM-RF in the study population. The Far North region had the highest prevalence of IgM-RF (9.8%) and the Littoral region had the lowest prevalence (3.2%). The prevalence of RF was 6.7% and 5.7% for females and males, respectively (sex ratio of 2.25). The IgM-RF prevalence was 9.7%, 8.9%, 9.1%, and 27.8% in participants with positive serological results for HIVAb, HBcAb, HBsAg, and HCV, respectively. Conclusion: Infection by HIV and HBV showed to poorly stimulated IgM-RF production. However, IgM-RF was highly produced in HCV infected participants. Increased IgM-RF production may contribute to cytotoxicity in tissues or organs of HCV-infected patients, leading to the onset of autoimmune diseases.